2022
DOI: 10.1021/acs.langmuir.1c03127
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Driven Highly Selective CO2 Reduction to CH4 Using Potassium-Doped g-C3N5

Abstract: Establishment of an efficient and robust artificial photocatalytic system to convert solar energy into chemical fuels through CO2 conversion is a cherished goal in the fields of clean energy and environmental protection. In this work, we have explored an emergent low-Z nitrogen-rich carbon nitride material g-C3N5 (analogue of g-C3N4) for CO2 conversion under visible light illumination. A significant enhancement of the CH4 production rate was detected for g-C3N5 in comparison to that of g-C3N4. Notably, g-C3N5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Layer double hydroxide loaded on exfoliated g-C 3 N 5 was also reported in the literature with enhanced catalytic results of NH 3 production yield at 2.523 mmol g −1 h −1 . [69] This research also confirmed the role of nitrogen vacancies in g-C 3 N 5 networks, working as an active site for the adsorption and activation of N 2 , which could facilitate the production yield.…”
Section: Nitrogen Fixationsupporting
confidence: 64%
“…Layer double hydroxide loaded on exfoliated g-C 3 N 5 was also reported in the literature with enhanced catalytic results of NH 3 production yield at 2.523 mmol g −1 h −1 . [69] This research also confirmed the role of nitrogen vacancies in g-C 3 N 5 networks, working as an active site for the adsorption and activation of N 2 , which could facilitate the production yield.…”
Section: Nitrogen Fixationsupporting
confidence: 64%
“…Hence, the UPS study is properly corroborating with the Mott–Schottky measurements. [ 20 ] Apparently, the E cb value of Bi 19 S 27 Cl 3 is sufficient to reduce CO 2 into CH 3 OH and CH 3 CH 2 OH and barely capable of producing CO (Figure S9, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 293.0 eV raised due to the presence of the p-p* conjugation of g-C 3 N 5 . 19,33 The N 1s spectrum had three peaks at 398.2, 400.7 and 403.8 eV, which corresponded to C-NQC-bonds, [N-(C) 3 ] and p-p* conjugation 25,30,32 (Fig. 4c).…”
Section: Morphology and Structural Informationmentioning
confidence: 99%
“…4a) proved that sample 3SCN consists of C, N, Cd and S. The result was consistent with the EDX elemental mapping, which further confirmed the existence of g-C 3 N 5 and CdS in the 3SCN composites. There were three peaks in the C 1s spectrum at 284.6, 286.2, and 287.9 eV, which were allocated to adventitious C, N 2 -CQN-and C-CH 2 , respectively 25,32 (Fig. 4b).…”
Section: Morphology and Structural Informationmentioning
confidence: 99%